2015
DOI: 10.4172/2157-7099.s3-019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP-2, MMP-9, MMP-14, TIMP-1, TIMP-2 in Intraepithelial and Invasive Cervical Neoplasia

Abstract: Aim: To evaluate the expression of MMP-2, MMP-9, MMP-14, TIMP-1 and TIMP-2 in Cervical intraepithelial neoplasia grade 3 (CIN 3) and invasive squamous cell carcinoma. Methods and Results:This study comprised three groups: Group 1: 55 cases with CIN 3; Group 2: 30 cases with CIN 3 and invasive carcinoma components; Group 3: 46 cases with invasive carcinoma. Protein expression was investigated in tumor and stromal cells by immunohistochemistry and percentages of immunostained cells were determined. The mean perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The immunohistochemical analyses for MMP-2, MMP-9, MMP-14, TIMP-1, TIMP-2, and VEGF-A were performed as described previously by Westin et al through hot spots areas [25,26]. Total cells and immunostained cells (stromal and tumor cells separately) were counted by two observers using morphometric software (Image-Pro Plus®, version 6.3, Olympus).…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%
“…The immunohistochemical analyses for MMP-2, MMP-9, MMP-14, TIMP-1, TIMP-2, and VEGF-A were performed as described previously by Westin et al through hot spots areas [25,26]. Total cells and immunostained cells (stromal and tumor cells separately) were counted by two observers using morphometric software (Image-Pro Plus®, version 6.3, Olympus).…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%
“…Our results showed an increase in MMP-9 + cells dispersion in HSIL and CC groups compared to control group, mainly in MS area, reinforcing the idea that together with MMP-2 and MMP-7, the adjacent tissue is preparing for tumor invasion. A study conducted by Westin et al (2015) demonstrated an increase of MMP-9 expression in stromal cells in all of groups (CIN I, CIN II and CIN III) compared to control group, suggesting that MMP-9 is related to interaction between the tumor and stromal cells. Corroborating with our results, Matheus et al (2014) reported an increase in MMP-9 + cells distribution in normal cells adjacent to dyskaryotic cells in cervical smear samples as lesion progressed, suggesting an induction of MMP-9 production by neighboring the tumor cells and the importance of cell-cell interaction during carcinogenesis.…”
Section: Discussionmentioning
confidence: 92%